Trimethylamine N-oxide, S-equol, and indoxyl sulfate inflammatory microbiota players in ocular Behcet's disease - Arslan, Sermal; Kaya, Mehmet Kaan; Aydin, Suna; Aydin, Suleyman (Walter de Gruyter Gmbh, 2025)
Objectives: The aims of the study were to assess the levels of serum TMAO, S-equol, and indoxyl sulfate in subjects with ocular active Beh & ccedil;et's disease (OABD) and ocular inactive Behcet's disease (OIBD). Methods: The study involved 22 patients with OABD, 22 patients with OIBD, and thwentythree control participants. 5 mL venous blood was taken from the participants. The TMAO, S-equol, and indoxyl sulfate in the serum were measured using the ELISA method. Results: When compared to the TMAO levels of the control group, the TMAO levels of the participants with OABD and OIBD were considerably greater (p<0.05). Similarly, when compared to the S-equol levels of the control group, the S-equol levels of the participants with OABD and OIBD were significantly higher (p<0.05). Additionally, when compared to the indoxyl sulfate of the control group, the indoxyl sulfate amounts of the participants OABD and OIBD were significantly higher (p<0.05). Conclusions: It was first time shown that microbiota molecules could have an impact on Beh & ccedil;et's disease (BD) pathogenesis. Additionally, measuring these molecules in addition to the BD Ocular Attack Score 24 (BOS24) might offer advice to medical professionals regarding the diagnosis and treatment of the illness.
Keywords: ocular Beh & ccedil;et's disease; TMAO; S-equol; indoxyl sulfate; microbiota